Try before you buy: experimental evidence on willingness to pay for tailored agricultural advice in Nigeria - Oyakhilomen Oyinbo; Chamberlin, Jordan; Maertens, Miet (Wiley, 2025)
Using a randomized controlled trial and a choice experiment in Nigeria, we examine the impact of a 2-year free provision of tailored advice through a digital decision support tool (DST) on farmers' willingness-to-pay (WTP) for a targeted decision support system. We find that farmers are willing to pay varying subscription fees to access different kinds of tailored advice. Also, we find that 2 years of exposure to DST-mediated interventions significantly increases farmers' WTP for tailored advice, particularly for soil fertility management and market information, but does not fully cover the costs of delivering such advice. On average, control farmers are willing to pay around 1-2 USD per year for different kinds of tailored advice, and treatment farmers are willing to pay 19%-85% more than the control in response to the interventions. In settings like ours, where there is limited viability of business models for DST-mediated advice that rely on full cost recovery from farmers, continued public support-through subsidized subscription fees and public investment in upscaling DSTs may be required, consistent with the public good nature of traditional agricultural extension.